GEOGRAPHIC DISTRIBUTION, ECOLOGICAL ADAPTABILITY AND AGRONOMIC STRATEGIES FOR BLACK PLUM (VITEX DONIANA SWEET) DOMESTICATION IN THE NIGERIAN SAVANNA - Babatunde, O.P.; Muyiwa, A.A.; Aremu-Dele, O.; Balogun, S.T.; Eban, D.O.; Olugbemi, Y.M.; Atolagbe, T.E. (Eurasian Journal of Applied Biotechnology, 2025)
Vitex doniana Sweet (Lamiaceae), commonly known as black plum, is a versatile tree species vital to Nigeria’s agroforestry systems, recognized for its nutritional, medicinal and ecological benefits. This comprehensive review synthesizes recent advances in the species geographic range, ecological preferences, morphological variation, propagation methods, phytochemical properties and conservation challenges, based on 83 georeferenced occurrence records from the Global Biodiversity Information Facility (GBIF) and studies published since 2010. The analysis shows Vitex doniana’s extensive presence across Nigeria’s savanna and forest zones, especially in Delta, Oyo and Taraba states, demonstrating its adaptability to a variety of habitats. Key findings include notable morphological diversity influenced by climatic and soil factors, promising propagation techniques and a diverse phytochemical profile supporting medical research. In addition to ecological understanding, the review incorporates agronomic considerations for domestication in Nigerian savannas, including soil management, nutrient application, water regulation, spacing, weed control and intercropping practices. These practical insights are essential for guiding large-scale cultivation and agroforestry integration. Challenges such as low seed germination, human activities and climate change continue to threaten the species' survival, calling for integrated strategies. This review recommends combining agroecological zoning, advanced propagation, agronomic standardization and community-led conservation to promote sustainable domestication and biodiversity protection in Nigeria.